The injustice of unfit clinical practice guidelines in low-resource realities - Nanna Maaløe, PhD; Anna Marie Rønne Ørtved, BSc; Jane Brandt Sørensen, PhD; Brenda Sequeira Dmello, MMED; Thomas van den Akker, ProfPhD; Monica Lauridsen Kujabi, MD; Hussein Kidanto, ProfPhD; Tarek Meguid, MMED; Ib Christian Bygbjerg, ProfDMSc; Jos van Roosmalen, ProfPhD; Dan Wolf Meyrowitsch, PhD; Natasha Housseine, PhD (Elsevier, 2021)
Summary: To end the international crisis of preventable deaths in low-income and middle-income countries, evidence-informed and cost-efficient health care is urgently needed, and contextualised clinical practice guidelines are pivotal. However, as exposed by indirect consequences of poorly adapted COVID-19 guidelines, fundamental gaps continue to be reported between international recommendations and realistic best practice. To address this long-standing injustice of leaving health providers without useful guidance, we draw on examples from maternal health and the COVID-19 pandemic. We propose a framework for how global guideline developers can more effectively stratify recommendations for low-resource settings and account for predictable contextual barriers of implementation (eg, human resources) as well as gains and losses (eg, cost-efficiency). Such development of more realistic clinical practice guidelines at the global level will pave the way for simpler and achievable adaptation at local levels. We also urge the development and adaptation of high-quality clinical practice guidelines at national and subnational levels in low-income and middle-income countries through co-creation with end-users, and we encourage global sharing of these experiences.